Barriers to entry and market coverage in vertically-differentiated markets. - Constantatos, Christos. (University of Ottawa (Canada), 1991)
We first derive the optimal price-quality choice of a protected multi-product monopolist operating in a market that could otherwise sustain two or more firms. The main results of this analysis is that in many instances the monopolist will choose not to serve the entire market even when the fixed entry cost is very low and the corresponding number of qualities marketed by the monopolist is very large. Next, we turn our attention to natural duopolies with single-product firms and we examine the implications of entry threats when entry is sequential. Neither is maximal differentiation a general outcome of such competition in the absence of entry threats, nor is minimal differentiation the necessary outcome when entry is contested. When the incumbent firms are facing entry threats, we show that the nature of the fixed cost can confer first mover advantages to the incumbent firms. Next we combine our previous results to examine whether an entry threat will induce a multiproduct monopolist to cover any parts of the market he/she would choose to leave unserved in the absence of such threat. We find that there are many cases where the uncovered market result is robust to the threat of entry. Our next concern is whether a strategic quality choice can protect the monopolist from entry without an increase in the number of qualities as well as whether such a choice can be superior, in terms of profits, to product proliferation. The answer to both questions is positive and the last issue of this thesis is how market coverage is affected by such a strategy. (Abstract shortened by UMI.)
Keywords: Economics, Commerce-Business.